Involvement of rural Malay youth in Malaysian herbal entrepreneurship - Paul, Kamal Chandra; Hamzah, Azimi; Abu Samah, Bahaman; Ismail, Ismi Arif; Alby, Jeffrey Lawrence D'Silva (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
Rural entrepreneurship is recognized as a primary engine of economic growth. The government of Malaysia is trying to increase the number of successful rural Malay herbal entrepreneurs nationwide. Therefore, the purpose of this study was to explore the involvement among rural Malay youth in herbal entrepreneurship in Malaysia. A qualitative approach using case study in-depth interview was used to gather data from ten rural herbal entrepreneurs. This study showed that in general Malay entrepreneurs are increasing gradually but technical based entrepreneurship is very low. It is suggested that the authorities of rural herbal development planners, government-link companies and other authorized agents need to focus on issues related to human capital, technical knowledge know-how and financial resources to increase the involvement of rural Malay youth herbal entrepreneurs.